If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14.73=g/4+12
We move all terms to the left:
14.73-(g/4+12)=0
We get rid of parentheses
-g/4-12+14.73=0
We multiply all the terms by the denominator
-g-12*4+(14.73)*4=0
We add all the numbers together, and all the variables
-1g+10.92=0
We move all terms containing g to the left, all other terms to the right
-g=-10.92
g=-10.92/-1
g=10+0.92/1
| -y+8=12 | | 6a-6=48 | | -8-16x=-936-48x | | 2+3x2*1=8 | | 6(m+3)=5(m-5) | | -r+6r-8÷4=8 | | -0.33+3p=-6.33 | | v/3-19=-15 | | 7a+25=100 | | -0.6+-g=-1.6 | | -30c=-210 | | 2/x+7=19 | | -1+8a=3a | | 0.75x-12=-3 | | X+16=8x-13 | | 9f+7=61 | | -10x-8x-87=183 | | 9x+8=100° | | 29-7m=-27 | | 2n+6n+4÷2=14 | | -4.8(6.3x-4.18)=58.6 | | 8k-5=3 | | 49f=−3 | | 2n+6n+4/2=14 | | 12=12+v−8/ | | 5d=-765 | | .35x=125 | | 8r+2=42 | | r/4+9=6 | | -7.5x+55.2=-15.3 | | 144x^2+120x-55=0 | | r/2+9=11 |